(untitled) (Revista de Crítica Literaria Latinoamericana, 2015)
"From 1958 to 1963, Roberto Juarroz published more than forty reviews in the cultural section of the journal La Gaceta (Tucumán), in those years one of the three most important journal in Argentina. In this article I compare the reviews with some of his poems published in the first Poesía vertical (1958). The critical analysis demonstrates that the same personal aesthetics pervades reviews and poems."